Probiotics for functional constipation in children: an overview of overlapping systematic reviews - Zhang, Yunxin; Li, Aiping; Qiu, Jing; Wen, Hua; Zhang, Hanwen; Sun, Xiangjuan (Frontiers in Cellular and Infection Microbiology, 2024)
Background: This overview of systematic reviews (SRs) and meta-analysis (MAs) aimed to systematically collate, appraise and synthesize evidence of probiotics for functional constipation (FC) in children.: SRs/MAs of probiotics for FC in children were systematic identified by searching Cochrane Library, PubMed, Embase, and Web of science. Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) were unitized by two reviewers independently to assess the methodological quality, reporting quality, and quality of evidence, respectively.Results: Seven SRs/MAs met the eligibility criteria and were included in this study. According to AMSTAR-2, a very low methodological quality assessment was given to the included SRs/MAs due to the limitations of items 2, 4 and 7. For the PRISMA statement, the overall quality of reporting was 2 unsatisfactory due to the lack of reporting on protocol, risk of bias across studies, synthesis of results, and additional analysis. According to GRADE, the quality of evidence for outcomes was rated as very low to moderate.Conclusions: Probiotics may be beneficial in improving FC in children. Because of limitations and inconsistent conclusions, further rigorous, normative and comprehensive SRs/MAs are needed to provide robust evidence for definitive conclusions.